Transport system equilibrium - Salava, Daniel; Švadlenka, Libor (Univerzita Pardubice, 2009)
Equilibrium in transport system is problem integrating itself some important aspects. Economical aspect by setting of transport system equilibrium is one of key parts of investigated problem. It means especially investigation of mutually related influence of macroeconomical and transport system each other. Other sight on equilibrium solves marketing problem of interaction of market cathegories in transport, thus transport demand and supply. Of course, technical and traffic provision face of transport system for its efficiency has the same importance. It is necessary of course for its perfect function to hold also relevant and adequate capability of transport infrastructure. This side of problem comprises thus spatial aspect, and that is why it is important to consider also possibilities of solution of interregional transportations equilibrium and next problem solution in context of transport network equilibrium. Modelling of these partial problems is naturally based on relevant factors, which influence directly and importantly particular areas of equilibrium and consequently it is possible to reflect them by means of mathematical expression. Problems of transport system equilibrium cannot be solved strictly in complex form, because there exist some various aspects of its solution. Economical viewpoint by setting of transport system equilibrium is one of parts of this problem, but important role for transport system efficiency is put also on technical and operational capaticies of this system, which requires for its function necessary of course sufficient infrastructure as well. This contribution otherwise comprises in previous text in general model form just possible solutions of system equilibrium from spatial viewpoint, thus reflects equilibrium solution of interregional or multiregional transportations, and next problem solution in sense of equilibrium on transport network. Modelling of this partial problems naturally works on relevant factors, which influence directly and significantly particular areas of equilibrium and simultaneously it is possible to express them by mathematical methods. The main goal and focusion of this paper is identification of relation between macroeconomical and transport system on basis of appropriately selected representative variables and then mathematical modelling of them from viewpoint of their mutual equal - balance state. Mission of solution results is not only verification of assumptions of concrete interaction between both systems, but on the basis of gained results also assessment of transport mode subsystems role in sense of their contribution to macroeconomical system. By transport system equilibrium modelling in relation to macroeconomical system, concrete data are applied from those final equilibrium model of both systems is derived including verification of its validity by means of relevant mathematical methods. Solution, detection and understanding to problem of relations between macroeconomical and transport system is created by appropriately selected representative variables of both systems and choice of structure and kind of enter data, which are quartal data of real gross domestic product in fixed prices of 2000 year and of traffic volumes in personal kilometres and tonal kilometres of passenger and freight transport for particular transport modes. Identification of mutual relation between selected variables of macroeconomical and transport system provides correlational analysis of stochastical components of time series. Before it, adequate smoothing and adjusting of data must be processed with verification of validity of gained results from used technique for smoothing. In cases, when correlation analysis confirms close dependences, regressional modelling is processed from viewpoint of mutual equilibrial state of both systems. State of variable of one system can also impact other system with certain delay, and that is why the attention is devoted also to delayed correlations of mutually inverse dependences with various time shifts. Results of regressional modelling including models followed from delayed correlations are veryfied by testing methods for examinations of regressional parametres and rate of explanation of reality by models. Mission of solution results is not only verifiation of assumptions of concrete interactions between both systems, but also assessment of role of partial transport modes to their support of economical system with additional ideas of causes.
Keywords: transport systems; equilibrium; macroeconomic system